Educational policies in response to the pandemic caused by the COVID-19 virus in Latin America: An integrative documentary review - Suyo-Vega, Josefina Amanda; Meneses-La-Riva, Monica Elisa; Fernández-Bedoya, Víctor Hugo; Alarcón-Martínez, Maricela; Ocupa-Cabrera, Hitler Giovanni; Alvarado-Suyo, Sofía Almendra; Polonia, Ana da Costa; Miotto, Angélica Inês (Frontiers in Education, 2022)
Educational policies in the face of the pandemic caused by the Covid-19 virus took an unexpected turn in Latin America. Virtuality constituted a key opportunity for the continuity of basic fundamental services in the citizen's right to education. The objective of this research was to analyze the educational public policies adopted by governments in Latin America in the face of the pandemic. The methodology was an integrative documentary review of the main international organizations whose documents provided relevant information on the actions to be implemented in fourteen Latin American countries. The results obtained show that the priority was to reestablish the continuity of educational services using mass communication resources, such as radio, television, digital platforms, making visible the inequity in the access to the Internet at home. It was also identified a deficiency in the competencies and digital resources of the educational community, dis-crimination and inclusion of people with some type of disability or different languages, especially in urban or rural areas because they do not have technological means. It was concluded that the educational policies in Latin America proposed during the Covid-19 period were designed with-out a real situational diagnosis in each country, to meet the demands of urban and rural areas in an equitable manner with the will of governments, providing budgets and resources that benefit the educational community, as an achievement of state policies